Mediterranean diet in the prevention of malignant diseases - Dulić Korina; Požar Hajnalka; Trajković Siniša (Association of Nurses Technicians and Midwives, 2023)
Malignant diseases represent a significant public health problem worldwide. Annually, over two million new cases are registered worldwide and over 4000 new cases in Serbia. The modern way of life characterized by sedentary behavior and improper diet have significant impact on the risk of disease, recurrence and survival. The role of nutrition is important in the prevention of malignant diseases. Fruits and vegetables (dietary fiber, vitamin C and E), omega-3 fatty acids have a protective effect by reducing oxidative stress and chronic inflammation. On the other hand, a high intake of sugar, saturated fatty acids, red and processed meat and alcohol are potential risk factors, increasing the level of circulating endogenous estrogen, insulin-like growth factor and cytokines. In the prevention of malignant diseases, the Mediterranean diet stands out, which shows the most significant effects in reducing the frequency and improving the survival of patients with malignant diseases.